Environmental risk assessment : a toxicological approach - Simon, Ted. (Boca Raton : CRC Press, 2020)
"This book explains how environmental risk assessment in particular is of increasing importance as a means of seeking to address the potential effects of chemicals in the environment in both the developed and developing world"--
OCLC-licensed vendor bibliographic record.
Keywords: Environmental risk assessment; Environmental toxicology; MEDICAL / Toxicology